Untapped Opportunities for the State Support of Agricultural Labour in Russia - Denisov, Viktor Ivanovich (Economy of Regions, 2018)
The focus of the article is the research of opportunities to improve the state support of the Russian Federation’s modern agriculture. The purpose of the study is to choose the most effective options for providing financial aid according to the indicators of its social and economic development. Moreover, we aimed to select the best ways of this financial aid’s distribution within areas and in the agricultural enterprises. The article highlights underestimated opportunities to increase the effectiveness of material and financial assistance to the agricultural sector. These opportunities do not consist uniquely in increasing financing but also in reasonable principles of using support funds by the agricultural enterprises. To this end, I propose to identify the directions of economic development, which are both profitable for an agricultural enterprise itself and meeting the goals of the overall social and economic development of the region and the interests of its population. Priority in obtaining state aid should be given to those enterprises whose production activities contribute to social and economic development of the region. The author’s multi-years research together with the scientists of the institutes of the Russian Academy of Agricultural Sciences and the Russian Academy of Sciences have allowed to identify the main reasons for the delay in the development of Russian agriculture in 2005-2016. In addition to the well-known negative impact of the shortage of funds and unfavourable natural conditions on the economy of agricultural enterprises, I found other reasons such as a weak development of the labour market and technologies, neglect of social, physical and industrial infrastructure. At the same time, the negative influence of these reasons is noticeably stronger than the negative influence of traditional factors. In this regard, the article proposes to improve the practice of allocating support funds. Funding should be used not only for on-farm, purely industrial needs but also for these enterprises’ social and economic development, as well as for the overall development of their region. I have applied the economic and statistical methods, analytic and computational algorithms processing a large amount of information on the development of agricultural production of the Russian Federation and foreign countries. As a result of the research, I propose areas for the improvement of state policy protecting agriculture. It will be useful to the regional authority and regional administrations, heads of the agricultural enterprises as well as scientific experts in the field of agricultural economics.